URBAN LANDSCAPE QUALITY AND FACTORS THAT HAVE INFLUENCE ON LANDSCAPE QUALITY IN LATGALE REGION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper deals with urban landscape individualities in the cities and towns of Latgale region. Also show facilities and methods of integrated assessment of urban landscape quality. Article provides information about specifics of urban landscape and factors, that have influence on landscape quality. The paper presents the results of Daugavpils and Rēzekne urban landscape quality complex assessment, that have been realised in 2003- 2005. This results don’t establish significant disparities between quality of urban landscape among Daugavpils and Rēzekne. This method of urban landscape assessment makes possible to get believeable and precise information about landscapes quality.